2003
DOI: 10.1002/pros.10245
|View full text |Cite
|
Sign up to set email alerts
|

ErbB1 and prostate cancer: ErbB1 activity is essential for androgen‐induced proliferation and protection from the apoptotic effects of LY294002

Abstract: These results suggest a model whereby androgens promote an increase in the activity of the epidermal growth factor (EGF)-network by increasing ErbB1 levels, and this activity of is essential for androgen-induced proliferation and survival of the prostate cancer LNCaP cell line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 27 publications
2
41
0
Order By: Relevance
“…8 Activated EGFR pathways are considered to belong to mechanisms that take over on development of androgen resistance. [42][43][44] Similarly, the IL-6 pathway has been suggested to play an important role in the development and growth of androgen-independent prostate cancer. 45 As shown before by others, [46][47][48] we also found that a short-term treatment with IL-6 inhibits growth of androgen-responsive LNCaP cells, whereas in androgen-unresponsive PC3 cells it evokes a growth stimulatory effect.…”
Section: Discussionmentioning
confidence: 99%
“…8 Activated EGFR pathways are considered to belong to mechanisms that take over on development of androgen resistance. [42][43][44] Similarly, the IL-6 pathway has been suggested to play an important role in the development and growth of androgen-independent prostate cancer. 45 As shown before by others, [46][47][48] we also found that a short-term treatment with IL-6 inhibits growth of androgen-responsive LNCaP cells, whereas in androgen-unresponsive PC3 cells it evokes a growth stimulatory effect.…”
Section: Discussionmentioning
confidence: 99%
“…Activated EGFR may induce distinct mitotic cascades, including the MAPK, PI3K/Akt, Shc, NF-κB and phospholipase Cg signalling pathways, which stimulate the proliferation, survival, motility and invasiveness of prostate cancer cells [29][30][31][32]. Elevated Akt activity may have a profound role in the progression of human prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have demonstrated the role of increased EGFR signaling in prostate carcinogenesis and progression (Sherwood et al, 1998;Ratan et al, 2003;Torring et al, 2003). We have recently reported the discovery of four somatic missense mutations in the tyrosine kinase domain of EGFR in prostate cancer patients (Douglas et al, 2006).…”
Section: Introductionmentioning
confidence: 99%